The Nutritional Status and Physical Freshness Review of SDN 013 Tambusai Utara Students’ - Wadyanti, Reny; Putra, Muarif Arhas; Sinurat, Ridwan; Putra, Riwaldi (Universitas Majalengka, 2024)
This research was motivated by the unknown data or information on the nutritional status and level of physical fitness of lower grade students at North Tambusai 013 State Elementary School. This study aims to determine the level of physical fitness and nutritional status of lower grade students at the North Tambusai 013 State Elementary School. The subjects in this research were lower grade students at North Tambusai 013 State Elementary School aged 7-9 years. This research is descriptive research, in this research the researcher only wants to describe the current situation without conducting hypothesis testing. The population used was 150 students taken by purposive sampling. Because the number of students in the sample is considered to represent the population of lower class students at North Tambusai State Primary School 013. The data collection technique uses the formula BMI=BB/TB2 and physical fitness uses the Indonesian Physical Fitness Test (TKJI) and for data analysis uses quantitative descriptive analysis expressed in percentage form. The descriptive analysis formula is p = f/nx 100%. The results of research on the nutritional status of North Tambusai 013 State Elementary School students in this study from 60 sample students obtained a frequency distribution of 19 students included in the thin category (31.66%), 33 students included in the normal category (55%), 6 students included in the obese category (10%), 2 students are included in the obese category (3.34%). Meanwhile, the results of the analysis of the physical fitness of students at the North Tambusai 013 State Primary School showed that the total frequency was 0 students (0.00%) in the very good category, 16 students (27%) in the good category, 19 students (31%) in the poor category, 25 students (42%) were in the medium category, and 0 students (0.00%) were in the very poor category. The highest frequency is in the medium category.